The Development of Kapiten’s Coffee in Building the Brand of Pasuruan Regency as an Agropolitan Area/Region - Yusuf, Mohammad Irsyad; Putra, Fadillah (Journal of Indonesian Tourism and Development Studies, 2022)
As a city with an identity, it tends to want to be recognized in the national, regional, and global markets either to get surplus value or as a leading brand in the international arena. Efforts to enter there require commercialization. So as to brand Kapiten coffee goods as the flagship of Pasuruan Regency and brands with quantifiable coffee quality, the idea of commercial is a calculated strategy. Commercialization involves the roles of academics, entrepreneurs (triple helix), and government, so Kapiten's Coffee succeeded in bringing Pasuruan Regency to the best coffee-producing area. In addition, commercialization is also an essential strategy for introducing Kapiten coffee products that are available on the open market both locally and internationally. The research method uses non-metric multidimensional and Critical Path, non-metric multidimensional scaling with ranking data analysis, which is the respondents' assessment of comparing Kapiten Coffee with other coffee brands. The critical path method is used to measure the duration of the work. Research results showed that Kapiten coffee has a superior taste, softer texture, and more attractive packaging, all of which are important strengths for Kapiten Coffee as an open marketer both domestically and abroad. The extensive marketing process for Kapiten coffee takes 51 days, starting from physical inspection of the coffee beans, followed by roasting, grinding, mixing, waste processing, primary and secondary packaging, product pricing, market price determination, marketing strategy preparation, and digital production. Keywords: City Branding, Commercialization, Kapiten Coffee, Stakeholder.